The Marginal Welfare Cost of Personal Income Taxation in New Zealand - John Creedy; Penny Mok (New Zealand Government, The Treasury, 2017)
The present paper reports estimates of welfare changes and the marginal welfare cost of income taxation for a wide range of income and demographic groups in New Zealand, in the context of a uniform increase in all marginal income tax rates. The results are obtained using enhancements to the NZ Treasury's behavioural microsimulation model, Taxwell-B, which uses discrete hours modelling to examine the labour supply responses of all individuals to an income tax change. Considerable variation is found in the marginal welfare costs for different groups, with an overall value of 12 cents per extra dollar raised. The paper also demonstrates the use of a money metric utility measure in a social welfare function evaluation. A smaller reduction in `social welfare' is obtained compared with the use of net incomes.
Keywords: H20; H31; I30; D63; 330; Direct taxation; excess burden; marginal welfare cost; welfare measurement; Einkommensteuer; Excess Burden; Wohlfahrtsanalyse; Direkte Besteuerung; Neuseeland